PEMBENTUKAN PORTOFOLIO OPTIMAL PADA SAHAM LQ-45 PERIODE TAHUN 2015 DENGAN MENGGUNAKAN SINGLE-INDEX MODEL - Erma Yuliaty; Erwin Dyah Astawinetu; Sri Hadijono (Universitas 17 Agustus 1945 Surabaya, 2019)
Investors basically pay more attention to risks than returns (profit rates). For this purpose,investors form a portfolio. A trusted portfolio can reduce risk and increase return. In forming aportfolio to reduce risk, it is expected to diversify. Due to rational investors, investors try to getan optimal portfolio, namely a portfolio that will produce the most minimal risk. Whereas ininvesting in the capital market, investors will be faced with many shares. The LQ-45 index is anindex containing 45 stocks with high liquidity and large capitalization. In connection with thismatter, in this study a research is conducted on the formation of an optimal portfolio using LQ45sharesandusingtheSingle-IndexModelapproach.Theresultsofthisstudyindicatethatoutof40LQ-45stocksthatsuccessfullyenteredastheresearchobject,10stockcandidateshavethepotentialto form an optimal portfolio. However, after being tested against Zi, only one stockwas chosen to form the optimal portfolio, namely AKRA shares. Thus AKRA's hundred percentshare becomes the optimal portfolio that generates returns of 0.2531% with a risk of 0.51%. Keywords: LQ-45 Index, Single-Index Model, optimal portfoli